Is Whistleblowing an Ethical Practice? - Nanang Shonhadji (Universitas Hayam Wuruk Perbanas, 2022)
Whistleblowing is susceptible to risks and ethical dilemmas in practice. It is not easy for members of an organization to become whistleblowers. The purpose of this study is to prove whether whistleblowing intention is a form of ethical practice. The empirical quantitative method was used for this study. The research samples were employees and auditors at the East Java Inspectorate. The use of Partial Least Square analysis techniques followed the collection of data through the distribution of questionnaires. The study results inform that whistleblowing intention was an ethical practice that was perceived and experienced by the whistleblower. Ethical sensitivity does not affect whistleblowing intention. In contrast, moral ethics, professional ethics, and ethical confidentiality affect whistleblowing intention. Ethical sensitivity has no effect because respondents believe that it is highly dependent on the sensitivity of the whistleblower’s attitude toward making decisions. The results of this study have contributed to strengthening the creation of a good whistleblowing system with definite legal protection guarantees provided by organizations and the state.